Production of Negative Hydrogen Ions Within the MMS Fast Plasma Investigation Due to Solar Wind Bombardment. Issue 8 (8th August 2018) - Gingell, Imogen; Schwartz, Steven J.; Gershman, Daniel J.; Paterson, William R.; Desai, Ravindra T.; Giles, Barbara L.; Pollock, Craig J.; Avanov, Levon A.
Abstract: The particle data delivered by the Fast Plasma Investigation instrument aboard National Aeronautics and Space Administration's Magnetospheric Multiscale (MMS) mission allow for exceptionally high‐resolution examination of the electron and ion phase space in the near‐Earth plasma environment. It is necessary to identify populations which originate from instrumental effects. Using Fast Plasma Investigation's Dual Electron Spectrometers, we isolate a high‐energy (approximately kiloelectron volt) beam, present while the spacecraft are in the solar wind, which exhibits an azimuthal drift with period associated with the spacecraft spin. We show that this population is consistent with negative hydrogen ions H − generated by a double charge exchange interaction between the incident solar wind H + ions and the metallic surfaces within the instrument. This interaction is likely to occur at the deflector plates close to the instrument aperture. The H − density is shown to be approximately 0.2–0.4% of the solar wind ion density, and the energy of the negative ion population is shown to be 70% of the incident solar wind energy. These negative ions may introduce errors in electron velocity moments on the order of 0.2–0.4% of the solar wind velocity and significantly higher errors in the electron temperature. Key Points: An anomalous population is observed by MMS's electron plasma instruments in the solar wind The population is consistent with negative ions generated by charge exchange within the instrument The errors in the calculation of the electron moments are estimated